(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Indian Premier League (IPL) is one of the most watched cricket events in the world, and both its viewership and its finances have significantly increased over the past few years. The Indian Premier League (IPL), which debuted in 2008 and is currently the most well-known T20 league worldwide, is played in India. Cricket is a tremendously fluid sport that evolves with each ball. People enjoy and watch cricket the most, and the Twenty20 format in particular since no one can predict the winner until the final ball of the final over. India’s most popular and frequently played sport, with the largest fan following, is cricket. The 20 overs formula used in the Indian Premier League is quite unexpected. Therefore, we decided to do an exploratory data analysis to research and evaluate the IPL games. The findings of the analytics applied reveal several insights from the IPL dataset that can be used to better optimize both team and individual performance.